Perencanaan Pembangunan Perumahan Di Kecamatan Kartosuro Kabupaten Sukoharjo Dilihat Dari Analisis Finansial Dan Analisis Ekonomi - Puspitasari, Marina Arica, Ir. H. Sri Sunarjono, MT., PhD, Ir. H. Nur Sahid, MM., MT, Moch. Solikin, ST., MT., PhD (2016)
Demand for houses in Sukoharjo regency, especially in Sub Kartosuro middling height, for the decision about the appropriateness of an investment, there should be a survey on the feasibility of investments that include aspects of the market, technical, social and economic aspects, legal aspects, and environmental aspects. For that reason the developers optimize the design of residential buildings were favored people with the management of development in terms of design calculations construction management forms are also to be known and planned overall costs involved in building housing. This case study visits of financial analysis and economic analysis aims to determine: nsideration of site selection by developers along with the site plan housing, setting the pace - step estimation of costs also time schedule development, and know the analysis of economic aspects in terms of Net Present Value (NPV), Profitability Index (PI), Payback Period (PP), and Internal Rate of Return (IRR). Based on the survey results in this investment will be built 55 units of residential houses with a total investment of Rp 21,651,305,727.45 old residential investment 24 months (2 years). Based on the count of the construction management will be planned for Time schedule completed construction of approximately 2 - 3 months. Based on the cost estimates can count RAB for homes with type 36 Rp 327,775,500.00; Type 41 Rp 367,928,000.00; type 45 Rp 383,723,500.00; and type 60 Rp 05,944,500.00. Thus, investment appraisal criteria Net Present Value (NPV), Profitability Index (PI), Payback Period (PP), and Internal Rate of Return (IRR) can be seen that the construction of housing projects Griya Asri is feasible to proceed.. Keywords : Internal Rate of Return (IRR), Net Present Value (NPV), Payback Period (PP), Profitability Index (PI)